Knuffle Bunny : a cautionary tale - Willems, Mo. (New York : Hyperion Books for Children, 2004)
A trip to the laundromat leads to a momentous occasion when Trixie, too young to speak words, realizes that something important is missing and struggles to explain the problem to her father.
Sequel: Knuffle Bunny, a case of mistaken identity.
K-3
460L
K
1.9
Keywords: Lost and found possessions -- Fiction; Toys -- Fiction; Fathers and daughters -- Fiction; Self-service laundries -- Fiction; Lost and found possessions -- Fiction; Toys -- Fiction; Fathers and daughters -- Fiction; Caldecott honor book